Detection of Seoul virus in wild brown rats (Rattus norvegicus) from pig farms in Northern England. (27th April 2019) - Murphy, Ellen G; Williams, Nicola J; Bennett, Malcolm; Jennings, Daisy; Chantrey, Julian; McElhinney, Lorraine M
Abstract : Introduction: Hantaviruses are maintained by mammalian hosts, such as rodents, and are shed in their excretions. Clinical disease can occur in humans from spillover infection. Brown rats ( Rattus norvegicus) are the globally distributed reservoir host of Seoul virus (SEOV). Human cases of SEOV‐associated haemorrhagic fever with renal syndrome (SEOV‐HFRS)have been reported in Great Britain (GB) since 1977. Methods: Brown rats (n=68) were trapped from a variety of peridomestic locations, with a focus on pig farms. Kidney and lung tissues were tested for viral RNA using a pan‐hantavirus RT‐PCR assay followed by Sanger sequencing and analysis. Results: SEOV RNA was detected in 19 per cent (13/68, 95% CI 11 to 30) of rats and all sequences fell within SEOV lineage 9. Twelve sequences were highly similar to each other and to the previously reported GB Humber strain of SEOV (98 per cent). One rat SEOV sequence was more distant. The SEOV prevalence in rats from pig farms was significantly greater (p=0.047) than other sites sampled. No significant sex or age differences were observed among positive and negative rats. Discussion: The results from this study suggest that SEOV could be widespread in wild rats in GB and therefore pose a potential risk to public health.